SISTEM KEAMANAN JARINGAN KOMPUTER MENGGUNAKAN METODE WATCHGUARD FIREBOX PADA PT GUNA KARYA INDONESIA - Sugiyono Sugiyono (STIKOM CKI, 2016)
Computer network security as part of an information system is very important to maintain the validity and integrity of data and ensure the availability of services for users, because the computer network systems should be protected from all sorts of attacks and intrusion at temps or scanning by unauthorized parties. Computer connected to the network, there are many security threats that are larger than on the host or a computer disconnected anywhere, so by controlling network security, the risk can be reduced, so that a network is designed as a data communication high way with the aim of increasing access to computer systems, while security is designed to control access, so that the provision of network security is a balancing act between open access with security. Firewalls are a means of controlling what information is allowed to get in and out of the local network and generally host or computer firewall connected to the internet and local LAN, and LAN access to the Internet only allowed through the firewall, so that with the help of the firewall can control security systems of computer networks of what is received and sent by the Internet and LAN. There are several types and methods in the firewall settings, through code firewall scan be built directly into the kernel, such as aid ipfw adm user space makes it possible to change the type of network traffic or by recording the types of network traffic, so that method of setting the firewall can use aid equipment of M400 watch guard.